Implementation Of Kiai's Leadership Style In Improving Teacher Creativity At The Jawahirul Hikmah Islamic Boarding School Tulungagung - Muharyanto, Agus; Patoni, Achmad; Efendi, Nur (International Journal of Educational Research & Social Sciences, 2022)
The research in this dissertation is motivated by the kiai as the leader of the pesantren which is an interesting leadership phenomenon. Kiai and teachers innovate with various forms of activities. Kiai improves the quality of Human Resources (HR) for teachers/asatidz and administrators, by instilling faith in the hearts of every student, administrator and board of Asatidz with a sincere attitude of lillahi ta'ala, riyadhoh, uswatun hasanah (exemplary) and patient; changing the mindset of asatidz, developing teacher skills and introducing and strengthening all institutional rules, duties, rights and obligations of asatidz, both as citizens of Islamic boarding schools, communities and citizens. The research approach uses qualitative methods. Data collection techniques are participant observation, in-depth interviews and documentation. The data analysis techniques used are l) data condensation 2) data presentation, 3) conclusion drawing/verification. From the results of this study, it can be concluded that: 1) Ithe implementation of the kiai leadership style in increasing teacher creativity at the Jawahirul Hikmah Islamic Boarding School Tulungagung is carried out by: a) Visionary leadership style is carried out with the kiai being the direction setter, agent of change,good mentor and role modelthe spirit of jihad and the spirit of fighting for and advancing the Jawaahirul Hikmah Islamic boarding school by forming a team in the management of educational institutions and collaborating with external parties in learning activities. b) The entrepreneurial leadership style is carried out by the kiai forming an entrepreneurial organization for Marble mining, carp and catfish farming, freshwater lobster cultivation, AQUAQY Factory to increase teacher creativity. c) Style,Innovative leadership by: (1) Kiai forming Marble mining entrepreneurship organizations, carp and catfish farming, freshwater Lobster cultivation, AQUAQY Factory to increase teacher creativity, (2) Kiai providing guidance by forming small groups with a quarantine model, (3 ) Outdoor class by making small groups in learning. d) Charismatic leadership style consists of: (1) belief in the kiai in providing policies, there are directions and instructions for program implementation to teachers/asatidz and administrators. (2) the kiai in his leadership involves members/followers and gives confidence to his members through all activities. (3) Leaders focus on the performance of their subordinates by providing motivation by providing complex, challenging, initiative, risk so that members become more responsible and diligent. e) The democratic leadership style provides the freedom to accept suggestions, thoughts, ideas from teachers to improve the existing programs at the Jawaahirul Hikmah Islamic Boarding School.